Dominance of Financial Ratios to ROE At PT Bank Muamalat Indonesia Tbk - Husni Mubarok; Akhris Fuadatis Sholikha; Safrina Muarrifah; Hendra Lesmana (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This research aims to understand the statistical results of the effect of CAR, FDR, NPF Net, ROA on ROE at PT Bank Muamalat Indonesia Tbk in 1999-2020. This study utilizes a descriptive method with a quantitative case study pattern design where the partial hypothesis test results that have been carried out by Analyzing Linear Regression model Coefficients of ROA Standardized Coefficients Beta component show the most influence of 0,831 able to explain 83,1% of the level of powerful relationship between the dependent variables and the remaining 16,9% is influenced by other variables, TCount 9,473 > TTable 2,07387 there is a significant effect of the value of 0,000 < 0,050 the hypothesis is accepted normally distributed residuals on ROE. The results of simultaneous hypothesis testing that have been carried out based on the Analyzing Linear Regression Model Summary table show that together the independent variable components of 0,946 are able to explain 94,6% of the very strong relationship between the dependent variable and the remaining 5,4% is influenced by other variables, FCount 36,291 > FTable 2,96 there is a significant effect of the value of 0,000 < 0,050 the hypothesis is accepted that the residual is normally distributed on ROE.